Effect of Feeding Criteria on Growth, Development and Productivity of Early Ripening Potato Varieties (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
The effect of feeding criteria on the growth, development, and productivity of early ripening potato varieties is an important aspect of potato cultivation that can significantly impact yield and quality. Different feeding criteria refer to the selection of fertilization methods, nutrient management practices, and timing of nutrient application.